Respuesta :

The first answer choice is your answer :)

Answer:

[tex]f^{-1}(3)=2[/tex] is correct

Step-by-step explanation:

Given the function [tex]f(x) = \log_2(x + 6)[/tex]

We need to find [tex]f^{-1}(3)[/tex]

First we find the inverse of the function

[tex]y= \log_2(x + 6)[/tex]

Switch x and y

[tex]x= \log_2(y + 6)[/tex]

Solve for y

[tex]2^x=y + 6[/tex]

[tex]y=2^x-6[/tex]

[tex]\therefore, f^{-1}(x)=2^x-6[/tex]

Put x=3

[tex]f^{-1}(3)=2^3-6\Rightarrow 8-6=2[/tex]

Thus, [tex]f^{-1}(3)=2[/tex] is correct

ACCESS MORE